Tahiti beyond the postcard : power, place, and everyday life - Kahn, Miriam (Culture, place, and nature., 2011)
The "Tahiti" that most people imagine -- white-sand beaches, turquoise lagoons, and beautiful women -- is a product of 18th century European romanticism and persists today to serve as the bedrock of Tahiti's tourism industry. This postcard image, however, masks a different, less known reality. French Polynesia remains a colony of France in the 21st century and was the site of France's nuclear testing program for nearly thirty years. The dreams and desires, which the tourism industry promotes, distract from the medical nightmares and environmental destruction caused by nuclear testing. Tahitians see the burying of a bomb in their land as deeply offensive. For them, the land abounds with ancestral fertility and genealogical identity, providing them with a constant source of both physical and spiritual nourishment. The imagined and lived perspectives of Tahiti seem incompatible, yet are intricately intertwined in the political economy of French Polynesia. This book engages with questions about the ways in which power entangles itself in place-related ways. How does colonialism perpetuate and exploit these images? How can nuclear weapons testing exist in a place that is promoted as a pristine paradise? How and why is 'Tahiti' crafted by a tourism industry whose goal is to create desire? How is this imagined product embraced, ignored, or sabotaged by Tahitians? The author uses interpretive frameworks of both Tahitian and European scholars, drawing upon ethnographic details that include ancient chants, picture postcards, antinuclear protests, popular song lyrics, and the legacy of Paul Gauguin's art, to provide fresh perspectives on colonialism, tourism, imagery, and the anthropology of place.